2018
DOI: 10.1016/j.visres.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of intraocular scatter on stereopsis

Abstract: To investigate the effect of intraocular scatter on stereopsis, we measured stereoacuity with scatter either remaining at the natural eye-induced level or further enhanced by a set of three different scatter filters. Stereo thresholds at different viewing durations were obtained using a psychophysical method of constant stimuli. The results indicate that stereoacuity was degraded with a binocular increase in scatter levels for all the subjects. Measurements were also performed in the presence of interocular di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
3
3
0
Order By: Relevance
“…Regarding induced visual impairment, all binocular visual functions (visual acuity, contrast sensitivity, discrimination capacity and stereopsis) were negatively influenced by the three filter conditions (BPM2 on the dominant eye and BF_0.8 on the dominant and both eyes), with the greatest impairment being obtained with the BF_0.8 foil on both eyes and the least impairment with the BPM2 fog filter on the dominant eye. This was in accordance with other studies [27,42,91] corroborating the negative influence of intraocular scattering induced by filters on binocular vision. Although, as far as we know, our study is the first to consider the combined effects of alcohol consumption and penalizing filters (BPM2 and BF_0.8) on the binocular vision alteration.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Regarding induced visual impairment, all binocular visual functions (visual acuity, contrast sensitivity, discrimination capacity and stereopsis) were negatively influenced by the three filter conditions (BPM2 on the dominant eye and BF_0.8 on the dominant and both eyes), with the greatest impairment being obtained with the BF_0.8 foil on both eyes and the least impairment with the BPM2 fog filter on the dominant eye. This was in accordance with other studies [27,42,91] corroborating the negative influence of intraocular scattering induced by filters on binocular vision. Although, as far as we know, our study is the first to consider the combined effects of alcohol consumption and penalizing filters (BPM2 and BF_0.8) on the binocular vision alteration.…”
Section: Discussionsupporting
confidence: 93%
“…One of these factors is the interocular differences (differences between the two eyes concerning a determined ocular parameter) which negatively disturb binocular vision. Increased interocular differences lead to that deterioration through decreased binocular summation [26,27,[34][35][36][37] and the impairment in stereopsis [27,[38][39][40][41][42]. For instance, in clinical applications, Jimenez et al [43] referred that increased interocular differences in corneal asphericity induced by refractive surgery, such as LASIK (Laser-Assisted in Situ Keratomileusis), impaired binocular visual performance (stereopsis).…”
Section: Of 20mentioning
confidence: 99%
“…Intraocular scattering is responsible for deterioration of the visual parameters and retinal image. These findings are line with Zhao et al, 29 who found deteriorated stereoacuity induced by three different scatter filters placed binocularly before the eyes (Pro-Mist 1/2, Pro-Mist 1, Pro-Mist 2), suggesting a mutual influence between incremental interocular differences in scatter and deterioration of stereoacuity. Similar to Zhao et al, who assessed interocular differences in scattering on stereopsis, the present study evaluated and provided additional information to characterise objectively the scatter level induced (by means of ocular parameters such as OSI, RS, MTF cut-off and log(s)).…”
Section: F I G U R Esupporting
confidence: 92%
“…So et al 28 reported that interocular differences in visual acuity result in a deterioration in stereopsis. Further, increased interocular differences in scatter levels will negatively affects stereopsis 29 . Jimenez et al 30 observed that interocular differences in corneal asphericity following refractive surgery could reduce binocular visual performance, even if the subjects were emmetropic post‐surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation